1975
DOI: 10.7326/0003-4819-83-4-503
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Manifestation of "False" Mitral Stenosis That Was

Abstract: An unusual normal posterior direction of motion of the posterior mitral valve leaflet echo during diastole was detected in a patient whose clinical and hemodynamic data confirmed the presence of significant rheumatic mitral stenosis after other conditions causing echocardiographic pattern of "false" mitral stenosis were ruled out. The finding of normal direction of motion of the posterior mitral valve leaflet when associated with abnormal EF slope of the anterior mitral valve leaflet does not rule out the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
3

Year Published

1977
1977
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…These patterns of movement of the posterior leaflet were observed by other investigators who concluded that posterior movement excluded the diagnosis of mitral stenosis (Feigenbaum, 1972;Teichholz, 1975). However, posterior movement was subsequently reported in patients with mitral stenosis (Berman et al, 1975;Cope et al, 1975;Flaherty et al, 1975;Levisman et al, 1975;Ticzon et al, 1975;Feigenbaum, 1976;Henry and Kastl, 1977). A controversy therefore exists in the use of analysis of the pattern of movement of the posterior leaflet, and this is partly because the underlying mechanism is unexplained.…”
Section: Discussionmentioning
confidence: 73%
“…These patterns of movement of the posterior leaflet were observed by other investigators who concluded that posterior movement excluded the diagnosis of mitral stenosis (Feigenbaum, 1972;Teichholz, 1975). However, posterior movement was subsequently reported in patients with mitral stenosis (Berman et al, 1975;Cope et al, 1975;Flaherty et al, 1975;Levisman et al, 1975;Ticzon et al, 1975;Feigenbaum, 1976;Henry and Kastl, 1977). A controversy therefore exists in the use of analysis of the pattern of movement of the posterior leaflet, and this is partly because the underlying mechanism is unexplained.…”
Section: Discussionmentioning
confidence: 73%
“…Though the patients with the mildest mitral stenosis were in this group, 2 patients had a mitral valve area below 1-3 cm2 and 5 required mitral valvotomy (Table 1). It has been suggested that such patients may have the cuspal rather than the commissural form of mitral stenosis (Ticzon et al, 1975). Nevertheless, the mitral echocardiograms of these patients were abnormal in that during atrial systole late diastolic movement of the posterior mitral valve leaflet was anterior.…”
Section: Discussionmentioning
confidence: 96%
“…1). Posterior movement is seen with normal valves, and also in the pseudomitral stenosis of decreased left ventricular compliance, but has also been shown in true mitral stenosis (Flaherty et al, 1975;Ticzon et al, 1975).…”
mentioning
confidence: 89%
“…Noninvasive evaluation by echocardiography would be an advantage if the technique could be shown to be reliable. Classical features such as a reduced diastolic closure rate and anterior movement of the posterior mitral leaflet are not sufficiently sensitive to enable diagnosis of lesser degrees of residual mitral stenosis to be made (Cope et al, 1975;Ticzon et al, 1975). We recently reported a new echocardiographic index of mitral valve closure that correlates well with the haemodynamically determined mitral valve area in patients with dominant mitral stenosis (Shiu, 1977).…”
mentioning
confidence: 99%